Gait Deviations in Children With Osteogenesis Imperfecta Type I. Issue 8 (September 2019) - Garman, Christina R.; Graf, Adam; Krzak, Joseph; Caudill, Angela; Smith, Peter; Harris, Gerald
Abstract : Background: Osteogenesis imperfecta (OI) is a congenital connective tissue disorder often characterized by orthopaedic complications that impact normal gait. As such, mobility is of particular interest in the OI population as it is associated with multiple aspects of participation and quality of life. The purpose of the current study was to identify and describe common gait deviations in a large sample of individuals with type I OI and speculate the etiology with a goal of improving function. Methods: Gait analysis was performed on 44 subjects with type I (11.7±3.08 y old) and 30 typically developing controls (9.54±3.1 y old ). Spatial temporal, kinematic, and kinetic gait data were calculated from the Vicon Plug-in-Gait Model. Musculoskeletal modeling of the muscle tendon lengths (MTL) was done in OpenSim 3.3 to evaluate the MTL of the gastrocnemius and gluteus maximus. The gait deviation index, a dimensionless parameter that evaluates the deviation of 9 kinematic gait parameters from a control database, was also calculated. Results: Walking speed, single support time, stride, and step length were lower and double support time was higher in the OI group. The gait deviation index score was lower and external hip rotation angle was higher in the OI group. Peak hip flexor, knee extensor and ankle plantarflexor moments, and power generation at the ankle were lower in the OI group. MTL analysis revealed no significant length discrepancies between the OI group and the typically developing group. Conclusions: Together, these findings provide a comprehensive description of gait characteristics among a group of individuals with type I OI. Such data inform clinicians about specific gait deviations in this population allowing clinicians to recommend more focused interventions. Level of Evidence: Level III—case-control study.